The Influence of Classpoint Media on the Learning Motivation of Physics Education Study Program Students - Muliani, Desy Eka; Azmi, Khairul; Alius, Mutia; Sulvayenti, Agnes; Amelia, Lona (Kasuari: Physics Education Journal (KPEJ), 2024)
Educators must address low motivation in Physics learning, and technological advancements offer solutions to engage students actively. This research investigates the impact of using Classpoint on student motivation in Physics courses. Employing quantitative research with a quasi-experimental design, the study focuses on first-semester students in the physics education program at Adzkia University. Data analysis, conducted using SPSS and the one paired sample t-test, reveals a significant increase in student learning motivation (p = 0.001) post-implementation of Classpoint. These findings highlight the effectiveness of interactive learning media like Classpoint in enhancing student motivation, emphasizing the potential for developing such tools to elevate the quality of education in the digital age.